2021
DOI: 10.3390/ijerph18168602
|View full text |Cite
|
Sign up to set email alerts
|

Using Latent Class Analysis to Identify Health Lifestyle Profiles and Their Association with Suicidality among Adolescents in Benin

Abstract: Youth suicidality is considerably prevalent in low- and middle-income countries, including Benin. Factors such as psychosocial distress, socio-environmental factors, and health risk behaviors are associated with suicidality. However, little is known about how these factors co-occur in these countries. An analysis of these factors taken together would help to identify the profiles most at risk and better target prevention policies. Our study aimed to identify profiles related to these factors and their associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…17 However, the prevalence of suicide attempts in this study is lower than the 22.2%, 18.5% and 23.2% reported in schoolbased surveys in Ghana, Mozambique and Benin respectively. 18,19,20 The higher prevalences may be attributed to higher proportion of participants: younger than 18 years; and anxiety and bullying experienced in the previous studies.…”
Section: Discussionmentioning
confidence: 81%
“…17 However, the prevalence of suicide attempts in this study is lower than the 22.2%, 18.5% and 23.2% reported in schoolbased surveys in Ghana, Mozambique and Benin respectively. 18,19,20 The higher prevalences may be attributed to higher proportion of participants: younger than 18 years; and anxiety and bullying experienced in the previous studies.…”
Section: Discussionmentioning
confidence: 81%
“…For instance, evidence from 59 LMICs reported a prevalence of 17% [25]. Also, a previous study in Benin reported the prevalence of suicide behaviour as 20% [10].…”
Section: Introductionmentioning
confidence: 99%
“…To a greater extent, conceptualising the factors that are linked to adolescent suicidal behaviours is crucial for mental health promotion and suicide prevention. Additionally, recent studies on suicidal behaviour among adolescents in Benin have not fully conceptualised these protective and risk factors from the broader socio-demographic and psychosocial characteristics of participants [5,10]. Therefore, this study sought to examine extensively multidimensional factors that serve as associated protective or risks for adolescent suicidal behaviour among adolescents in Benin.…”
Section: Introductionmentioning
confidence: 99%
“…The cut-off point for PHQ-9 is 10 points which could identify high-risk individuals for depression episodes ( 3 ). Yet trajectories of depressive episodes are complicated and might originate from the interaction of internal and external factors, including genetic, psychological, and environmental risk factors ( 4 ). Early screening of depressive symptoms by cut-off value may decrease the sensitivity of the screening test.…”
Section: Introductionmentioning
confidence: 99%